Divided, they win? a case study of the new political generation in Egypt since 25th January 2011 - El-Banna, Sanaa (AUC Knowledge Fountain, 2012)
This dissertation explores the political culture of the new political generation in Egypt after 25th January 2011. It aims at examining the reasons behind generational conflicts on the new political landscape. It defines political generation as â a group of people who have been subject to common social and political (â ¦) influences and circumstances' that shape their political values, attitudes, and signify their sharing of an essential destiny' . Hence, generations are defined in terms of political culture, rather than age groups. The study examines six suggestive cases: The National Movement for Changeâ Kefayaâ , the 6th of April, the We Are All Khaled Saed, the Egyptian Current Party, the Salafyo Costa movement and Ultras Ahlawy football community. Through examining formative experiences, ideological composition and organizational forms, values, symbols, strategies, and inter-relationships, I aim at resolving one research problem: The significant variation within the political culture of the new generation deepens conflicts both within the emergent Generation and with the Muslim Brotherhoodâ on various ideological issues and political strategies. Also, it stimulates ideological transformation and threatens to upgrade political authoritarianism. In order to develop a 'grounded' , knowledge of the subject, the study, first, examines reasons behind the MB's failure to co-opt the new generation both before and after the 25th January. Secondly, It examines the formative socio-political experiences of each generational unit. Thirdly, I report the interview findings on ideological and organizational manifestations and, finally, I analyze the results in order to understand the reasons behind generational conflicts and how they might lead into upgrading Mubarak's authoritarianism. This research provides future studies with elementary background on the situation, its main actors, their inter-relationships and possible means of resolving their conflicts. I use two integrative methods of qualitative research: ethnographic semi-structured interviews with members of the new political generation and â participation as observer'. Data culled from primary and secondary sources is analyzed through conceptual analysis tool to examine the undergoing transformation and possible means to resolve the conflict. The study concludes that there are four intertwined lines through which generational conflicts evolved: a) problems either withered away or got replaced by new problems, b) a change and/or loss of leadership, mobilizable resources and sympathy, c) the rise of unexpected generational cooperation, and d) one generation topple or liquidate the other.